PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN MATEMATIK SISWA KELAS III SEKOLAH DASAR - Azamul Fadhly Noor Muhammad; Noer Intan Novitasari (Jurnal Bidang Pendidikan Dasar, 2020)
Abstract This research aims to develop ethnomatematics-based mathematics teaching materials that will be used in the learning process. This is intended to form patterns of understanding of the material and the concept of a flat shape in class III through objects or historic sites. Learning material is made based on literacy that is easily understood by students based on mathematical material and / or the application of mathematics that has entrenched the community environment. The subjects in this study were students of SDN Jenang 05 and SDN Mulyadadi 02 Class III Kec. Majenang Kab. Cilacap Jawa Tengah Academic Year 2018/2019. The use of mathematics teaching materials, teaching devices, and analysis of the lack of teaching materials used will become study material in development research that will produce a product that is mathematics teaching material based on ethnomatatics. The results of the research on ethnomatematics-based teaching material development can be seen from the pre-test assessment, more than 50% of students get a very low learning understanding category and below the specified KKM, which is 75 and post-test assessment results, 4 students with very high grades, 5 students with high grades, 10 students with medium grades, and 40 students with low grades but exceeding the KKM set. This means that students who are above the specified KKM, and Ethnomatic Mathematics-Based Teaching Materials that are developed effectively to improve student understanding of learning. Abstrak Penelitian ini bertujuan untuk mengembangkan bahan ajar matematika berbasis etnomatematika yang digunakan dalam pembelajaran. Hal ini dimaksudkan untuk membentuk pola pemahaman pada materi dan konsep bangun datar di kelas III melalui objek atau situs bersejarah. Materi pembelajaran dibuat berdasarkan literasi yang mudah dipahami siswa sesuai materi matematika atau penerapan matematika yang telah membudaya dilingkungan masyarakat. Subyek dalam penelitian ini adalah siswa SDN Jenang 05 dan SDN Mulyadadi 02 Kelas III Kec. Majenang Kab. Cilacap Jawa Tengah Tahun Pelajaran 2018/2019. Penggunaan bahan ajar matematika, perangkat pengajaran, dan analisis kekurangan bahan ajar yang digunakan nantinya menjadi bahan kajian dalam penelitian pengembangan yang akan menghasilkan sebuah produk yaitu bahan ajar matematika berbasis etnomatematika. Hasil dari penelitan pengembangan bahan ajar berbasis etnomatematika ini dilihat dari penilaian pre-test, lebih dari 50% siswa mendapatkan katagori pemahaman belajar sangat rendah dan dibawah KKM yang ditetapkan, yaitu 75 dan hasil penilaian post-test, 4 siswa dengan nilai sangat tinggi, 5 siswa dengan nilai Tinggi, 10 siswa dengan nilai sedang, dan 40 siswa dengan nilai rendah tetapi melebihi KKM yang ditetapkan. Artinya siswa yang berada diatas KKM yang ditetapkan, dan Bahan Ajar Berbasis Etnomatematika yang dikembangkan efektif untuk meningkatkan pemahaman belajar siswa.